1979
DOI: 10.3354/meps001001
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Variations in Microbiological and Chemical Parameters

Abstract: At three Baltic-Sea stations, short-term variations were monitored of a number of microbiological and chemical parameters. At two of these stations (Kampinge, Sweden; south-eastern Baltic Sea) uniform, individual water bodies were sampled at short intervals. Here, distinct patterns or rhythms could be demonstrated in the variation of microbiological and chemical parameters, obviously reflecting different ecological situations. In contrast, at the third station in the Kiel Fjord, no indication could be found of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 6 publications
7
30
0
1
Order By: Relevance
“…Studies of short-term variations in the bacterioplankton have clearly indicated that short-term factors control fluctuations in the numbers of bacteria (Meyer-Reil et al, 1979;, a conclusion that is in keeping with the capabilities of bacteria for rapid growth. Among these factors, the availability of dissolved organic substrate is certain to be of primary importance.…”
Section: Discussionmentioning
confidence: 89%
“…Studies of short-term variations in the bacterioplankton have clearly indicated that short-term factors control fluctuations in the numbers of bacteria (Meyer-Reil et al, 1979;, a conclusion that is in keeping with the capabilities of bacteria for rapid growth. Among these factors, the availability of dissolved organic substrate is certain to be of primary importance.…”
Section: Discussionmentioning
confidence: 89%
“…Vaccaro et al 1968;Hamilton and Preslan 1970;Hobbie et al 1972;Liebezeit et al 1980). The apparent utilization rate in the Gulf of Maine (dark bag) is 4-6 times rates of high-specific-activity glucose uptake from the offshore Baltic and North Seas (Billen et al 1980;Meyer-Reil et al 1979). Since glucose usually dominates the dissolved monosaccharide pool, this suggests the importance of the polysaccharide fraction in bacterial carbohydrate utilization.…”
Section: Lmnolmentioning
confidence: 99%
“…Populations of autotrophic microorganisms exhibit clear diel patterns in photosynthesis, cell growth and cell division in response to daily light cycles (Jacquet et al 1998, 2001. Additionally, diel variability in the supply of dissolved organic substrates and grazing intensity promotes daily shifts in the abundance, growth rate and production of heterotrophic bacterioplankton communities (Meyer-Reil et al 1979, Simon 1994, Torréton et al 1994, Shiah & Ducklow 1995, Gasol et al 1998, Hagström et al 2001.…”
Section: Introductionmentioning
confidence: 99%